UNIT 15D.3 Propagation, Quantification, Detection, and Storage of West Nile Virus. Issue 1 (5th November 2013) - Brien, James D.; Lazear, Helen M.; Diamond, Michael S.
Abstract: West Nile virus (WNV) is a member of the Flaviviridae family of enveloped, single‐stranded, positive‐sense RNA viruses. WNV, an emerging viral pathogen, is transmitted by mosquitoes to birds and mammals and is responsible for an increasing incidence of human disease in North America and Europe. Due to its ease of use in the laboratory and the availability of robust mouse models of disease, WNV provides an excellent experimental system for studying molecular virology and pathogenesis of infection by flaviviruses. Here, we describe common laboratory techniques used to propagate, quantify, detect, and store WNV. We also briefly describe appropriate safety precautions required for the laboratory use of WNV, which is classified as a Biosafety Level 3 pathogen by the United States Centers for Disease Control and Prevention. Curr. Protoc. Microbiol . 31:15D.3.1‐15D.3.18. ©2013 by John Wiley & Sons, Inc.